The relationship between visfatin and cardiac markers on induced myocardial infarction in rats - Erten, Mehmet; Cimenci, Iclal Geyikli; Kuloglu, Tuncay; Kalayci, Mehmet; Erten, Fusun (Academic Press Ltd- Elsevier Science Ltd, 2019)
Myocardial infarction (MI) is one of the most important reason of mortality into worldwide. Visfatin is a novel adipokine which was reported increased in metabolic syndrome and obesity. Moreover, it is known that visfatin increases in aterosclerotic endotelial dysfunction. In our study we want to demonstrate how visfatin changes in isoproterenol (ISO) induced MI. Rats were allocated into 4 groups in which each group included 6 rats in this study. 200 mg/kg ISO was administered into rats except control group to induce MI. I. and II. Group rats in 6th hour, III. Group rats in 24th hour and IV. Group rats in 7th day were decapitated. Visfatin was searched in cardiac tissues of all groups by immunohistochemistry stainning. Visfatin and cardiac markers' levels were measured in serum samples. Serum visfatin levels gradually increased in 6th and 24th hour in MI rats compared to controls. In 7th day visfatin levels decreased to control levels. These changes correlated with serum troponin T levels. These findings were supported by immunohistochemistry stainning of visfatin in cardiac tissues. It has been shown that visfatin could be useful in diagnosing MI and may be a biomarker for cardiac ischemia because of increasing in systemic circulation and cardiac tissues in MI like troponins.
Keywords: Myocardial infarction; Visfatin; Cardiac markers; Troponin